Molecular Characterisation Of Escherichia Coli Serogroup O 157:H7 - Mohd Dzomir, Ahmad Zainuri (1998)
Fourteen E. coli O 157:H7 beef isolates were characterised by using four specific epidemiological markers: combination of antibiogram and plasmid profiling, pulsed-field gel electrophoresis (PFGE) and arbitrary primed polymerase chain reaction (AP-PCR). These markers were assessed for their reliability, typability, rapidity and discriminatory power in differentiating beef E. coli O 157:H7 strains from different locations, namely Bangsar, Kajang, Petaling Jaya and Serdang. The majority of the isolates were resistant to penicillin G (100%), vancomycin (100%), trimethoprim/ sulphametoxazole (100%), bacitracin ( 1 00%) and erythromycin (92.8%). Only 21.4% were resistant to carbenicillin. 14.3% and 7.1% were resistant to ampicillin and cephalotin, respectively Plasmid analysis revealed three basic plasmid patterns among E. coli O 157:H7 strains, profile 1 characterised by plasmid DNA of 60 and 2.5 MDa, profile 2 characterised by plasmid of 60 MDa, and profile 3 characterised by the absence of any plasmid in the strains. Grouping according to combination of antibiogram and plasmid analysis indicated eight different groups as two strains with similar antibiotype could be distinguished into two different strains by their dissimilar plasmid profile. However, the reliability of antibiogram and plasmid analysis in typing E. coli O 157:H7 can be questioned. Thus, other reliable methods such as PFGE and AP-PCR were then applied. In the present study, macrorestriction of genomic DNA of E. coli 0 1 57:H7 using Xbal, SpeI and HindIII and analysed by PFGE successfully grouped ten out of fourteen isolates into five groups and provided evidence of epidemiologically related strains between strains of different and same locations. However, AP-PCR using three short primers grouped the isolates into fourteen distinct groups and differentiates isolates that were not differentiated by PFGE. The overall analysis of the present study revealed AP-PCR as the most suitable method to differentiate E. coli O 157:H7 because it was more discriminatory, less labor intensive and applicable to all isolates. Using this method, it was clearly shown that all fourteen E. coli O 157:H7 existed as independent isolates.